2021
DOI: 10.1177/07356331211056532
|View full text |Cite
|
Sign up to set email alerts
|

A Curation Activity-Based Self-Regulated Learning Promotion Approach as Scaffolding to Improving Learners’ Performance in STEM Courses

Abstract: Self-regulated learning (SRL) is an important method in STEM courses that can help learners acquire knowledge by discovering, organizing, and integrating materials. However, learners may not perform well without scaffolding, which results in purely participation in tasks without solid knowledge acquisition. To guarantee SRL effectiveness, scaffolding that can support learners’ knowledge discovery, organization and integration is needed when curation is introduced to support high-level cognition in STEM courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Hsiao et al (2022) show that STEM education is characterized by a student-centered approach which nurtures learners’ problem-solving, collaborative, and creative thinking skills. Compared with the traditional teacher-centered approach, where learners passively receive knowledge from a teacher, in the student-centered STEM method learners combine interdisciplinary knowledge and their personal experience to actively complete the construction of their own knowledge using practice and experiments (Christensen et al, 2015; Wang et al, 2022). These differences make traditional methods, which focus solely on the final learning outcome, increasingly unsuitable for student-centered STEM education.…”
Section: Introductionmentioning
confidence: 99%
“…Hsiao et al (2022) show that STEM education is characterized by a student-centered approach which nurtures learners’ problem-solving, collaborative, and creative thinking skills. Compared with the traditional teacher-centered approach, where learners passively receive knowledge from a teacher, in the student-centered STEM method learners combine interdisciplinary knowledge and their personal experience to actively complete the construction of their own knowledge using practice and experiments (Christensen et al, 2015; Wang et al, 2022). These differences make traditional methods, which focus solely on the final learning outcome, increasingly unsuitable for student-centered STEM education.…”
Section: Introductionmentioning
confidence: 99%
“…SRL support helps learners achieve academic success, and its importance is demonstrated by studies that have shown that learners who lack SRL support may not regulate their learning to obtain an adequate level of understanding when studying complex topics (Azevedo & Hadwin, 2005; Shin & Song, 2022; Wang et al, 2022). Various forms of computer-based scaffolding have been proposed, such as prompts, feedback, and integrated support systems.…”
Section: Literature Reviewmentioning
confidence: 99%